Congenital presentation of synchronous Atypical Teratoid Rhabdoid Tumor and Malignant Rhabdoid Tumor of the urinary bladder in a term infant - Tang, Vivian; Conner, Peter Michael; Tovar, Jason Paul; Gandour-Edwards, Regina Frances; Antony, Reuben; Bobinsk, Matthew; Edwards, Michael Steven Brent; Lechpamme, Mirna (Autopsy and Case Reports, 2020)
Atypical teratoid/rhabdoid tumor (AT/RT) is a rare central nervous system (CNS) tumor diagnosed primarily in infants and usually portends a poor prognosis. Despite being the most common embryonal tumor in children less than 1 year old, diagnosis is difficult to make based on clinical findings or imaging alone. A complete diagnosis of AT/RT requires identification of loss of integrase interactor 1 (INI1) protein or the SWI/SNF-related, matrix-associated, actin-dependent regulator of chromatin, subfamily b, member 1 (SMARCB1) gene, in its most common presentation. Moreover, their presentation with other primary rhabdoid tumors in the body raises significant suspicion for rhabdoid tumor predisposition syndrome (RTPS). We report a case of a one-month-old infant admitted for worsening emesis and failure to thrive, who was later found to have brain and bladder masses on radiologic imaging. Autopsy with subsequent immunoprofile and molecular testing were crucial in establishing the absence of INI1 nuclear expression and possible homozygous deletion of SMARCB1 in the urinary bladder tumor tissue. Sequencing of the peripheral blood demonstrated probable single copy loss at the SMARCB1 locus. The constellation of findings in tumor and peripheral blood sequencing suggested the possibility of germline single copy SMARCB1 loss, followed by somatic loss of the remaining SMARCB1 allele due to copy neutral loss-of-heterozygosity. Such a sequence of genetic events has been described in malignant rhabdoid tumors (MRT). Dedicated germline testing of this patient’s family members could yield answers as to whether rhabdoid tumor predisposition syndrome will continue to have implications for the patient’s family.